2021
DOI: 10.1302/2633-1462.211.bjo-2021-0128.r1
|View full text |Cite
|
Sign up to set email alerts
|

Deep infection after hip hemiarthroplasty: risk factors for infection and outcome of treatments

Abstract: Aims Deep surgical site infection (SSI) remains an unsolved problem after hip fracture. Debridement, antibiotic, and implant retention (DAIR) has become a mainstream treatment in elective periprosthetic joint infection; however, evidence for DAIR after infected hip hemiarthroplaty is limited. Methods Patients who underwent a hemiarthroplasty between March 2007 and August 2018 were reviewed. Multivariable binary logistic regression was performed to identify and adjust for risk factors for SSI, and to identify f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 27 publications
0
11
1
Order By: Relevance
“…6 Based on these guidelines, DAIR is often the treatment of choice since it is associated with less morbidity and therefore is perhaps more appropriate for this frail patient population. However, the results of this study, and others alike, [7][8][9][10][11]21,22 challenge this perception given the inferior treatment success rates of DAIR for HA PJI, which range from 22% to 82% (Table VI). In our study, DAIR was the most common treatment modality used (59%).…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…6 Based on these guidelines, DAIR is often the treatment of choice since it is associated with less morbidity and therefore is perhaps more appropriate for this frail patient population. However, the results of this study, and others alike, [7][8][9][10][11]21,22 challenge this perception given the inferior treatment success rates of DAIR for HA PJI, which range from 22% to 82% (Table VI). In our study, DAIR was the most common treatment modality used (59%).…”
Section: Discussionmentioning
confidence: 57%
“…7,8 Perhaps HA PJI should be managed by surgeons skilled in arthroplasty as they would be more likely to employ the optimal surgical strategy: single-stage revision arthroplasty with conversion to THA. Craxford et al 9 reported on patients who underwent surgical treatment (43 DAIR, seven excision arthroplasty) for surgical site infection following HA. They showed that stem exchange was not associated with improved treatment success.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, the reported success rates of debridement with prosthesis retention and long-term antibiotic use are found to be variable (21% to 89%). [4][5][6][7][8] The alternative is revision surgery, which has severe implications for the patient including prolonged hospitalization, high health and social costs, 9,10 and up to 10% risk of recurrence. 3 The latter is likely related to residual bacteria in the wound.…”
Section: Introductionmentioning
confidence: 99%